CORPORATE GOVERNANCE, SIZE AND FIRMS’ PERFORMANCE - RUSMIN RUSMIN (Jurnal Bisnis dan Akuntansi, 2012)
This study examines the performance of the entire population of Indonesian listed firms for years 2005 and 2006. The results show that Indonesian listed companies have a very low level of profit (as measured by ROA) of 3.73% and 20.70% of firms had losses with a larger percentage in the manufacturing sector. However, 58.48% of firms reported increase in profits from year 2005 to year 2006. This partly illustrates that these firms are still recovering from the Asian currency crisis. Regression analysis reveals that size of firm and levelof ownership concentration help predict performance. Larger firms with high ownership concentrated have higher profit levels. Interestingly, firm corporate governance attributes such as percentage of independentdirectors and independent of the audit committee were not significant predictors. This has significant implications for Indonesian companies since globally companies are moving towards a more regimentedcorporate governance structure to enhance firm productivity. Indonesian, similar to that of other developing countries seems to have a less effective system of corporate governance prompting calls for more directgovernment intervention especially between majority and minority shareholders.